Modeling the structure of the transmembrane domain of T1R3, a subunit of the sweet taste receptor, with neohesperidin dihydrochalcone using molecular dynamics simulation - Nakagita, Tomoya; Matsuya, Takumi; Narukawa, Masataka; Kobayashi, Takuya; Hirokawa, Takatsugu; Misaka, Takumi (Bioscience, biotechnology, and biochemistry, 2023)
ABSTRACT Neohesperidin dihydrochalcone (NHDC) is a sweetener, which interacts with the transmembrane domain (TMD) of the T1R3 subunit of the human sweet taste receptor. Although NHDC and a sweet taste inhibitor lactisole share similar structural motifs, they have opposite effects on the receptor. This study involved the creation of an NHDC-docked model of T1R3 TMD through mutational analyses followed by in silico simulations. When certain NHDC derivatives were docked to the model, His7345.44 was demonstrated to play a crucial role in activating T1R3 TMD. The NHDC-docked model was then compared with a lactisole-docked inactive form, several residues were characterized as important for the recognition of NHDC; however, most of them were distinct from those of lactisole. Residues such as His6413.33 and Gln7947.38 were found to be oriented differently. This study provides useful information that will facilitate the design of sweeteners and inhibitors that interact with T1R3 TMD. Graphical Abstract Graphical Abstract A neohesperidin dihydrochalcone docked model of transmembrane domain of T1R3 subunit of the human sweet taste receptor based on results of mutational analysis.